2022
DOI: 10.1002/iid3.723
|View full text |Cite
|
Sign up to set email alerts
|

Low serum level of 25‐OH vitamin D relates to Th17 and treg changes in colorectal cancer patients

Abstract: Background: Serum 25-hydroxyvitamin D [25(OH)D] level alters in colorectal cancer (CRC) development. Regulatory T (Treg) cells and T-helper type 17 (Th17) cells are involved in immune response. Th17-mediated proinflammatory responses contribute to tumorigenesis, and Treg plays different roles in different periods of CRC. Vitamin D deficiency is associated with significant variations in peripheral immune cells. This study investigated the relationship between Th17 and Treg cells and 25(OH)D level in CRC. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…It inhibits T-cell proliferation and promotes the induction of T-regulatory cells [ 43 , 44 ]. Consequently, inflammatory cytokines, such as interleukin 17 (IL17) and IL21, are decreased, while anti-inflammatory cytokines, such as IL 10, are increased [ 45 , 46 ]. Monocyte production of the inflammatory cytokines, including IL 1, IL 6, IL 8, IL 12, and tumor necrosis factor-α (TNFα), is inhibited in the presence of vitamin D [ 47 ], and it also inhibits the differentiation and maturation of the dendritic cells [ 48 ].…”
Section: Vitamin D and Immune Functionmentioning
confidence: 99%
“…It inhibits T-cell proliferation and promotes the induction of T-regulatory cells [ 43 , 44 ]. Consequently, inflammatory cytokines, such as interleukin 17 (IL17) and IL21, are decreased, while anti-inflammatory cytokines, such as IL 10, are increased [ 45 , 46 ]. Monocyte production of the inflammatory cytokines, including IL 1, IL 6, IL 8, IL 12, and tumor necrosis factor-α (TNFα), is inhibited in the presence of vitamin D [ 47 ], and it also inhibits the differentiation and maturation of the dendritic cells [ 48 ].…”
Section: Vitamin D and Immune Functionmentioning
confidence: 99%
“…VDR signaling pathway has a crucial role in several physiological activities, such as bone development, anti-inflammatory response, and anti-tumor activities ( Shang and Sun, 2017 ). Notably, a decrease in both the serum vitamin D levels and the expression of VDR in the colon has been observed in patients with colitis or colorectal cancer ( Chen and Jin, 2022 ; Ma et al, 2023 ). In a study using a mouse model of colitis-associated cancer, treatment with asperuloside was found to significantly enhance the expression of VDR in the colon, leading to marked reductions in colitis symptoms and a decrease in both the quantity and size of tumors ( Lu et al, 2022 ).…”
Section: Natural Bioactive Compounds Targeting Vdr Activitymentioning
confidence: 99%
“…7 VitD supplementation decreases Th1/Th17 and memory B cells, which contribute to SLE-related inflammation, and increases Treg cells, which inhibit SLE-related proinflammatory response. 8 Previous studies by our group have revealed that VitD can improve inflammation, immunity, and bone metabolism in SLE mice and can bind to its receptors to treat SLE by inhibiting Th cells, related factors, the microenvironment, and the production of autoimmune antibodies. 9,10 The Wnt signaling pathway has been extensively studied.…”
Section: Introductionmentioning
confidence: 99%
“…SLE is characterized by the hyperreactivity of B and T cells, loss of immune tolerance, overproduction of autoantibodies, and inflammation of multiple organ systems 7 . VitD supplementation decreases Th1/Th17 and memory B cells, which contribute to SLE‐related inflammation, and increases Treg cells, which inhibit SLE‐related pro‐inflammatory response 8 . Previous studies by our group have revealed that VitD can improve inflammation, immunity, and bone metabolism in SLE mice and can bind to its receptors to treat SLE by inhibiting Th cells, related factors, the microenvironment, and the production of autoimmune antibodies 9,10…”
Section: Introductionmentioning
confidence: 99%